Fragilidade de adultos e idosos com doença renal em tratamento hemodialítico : identificação de fatores associados - Gesualdo, Gabriela Dutra (2016)
Introduction: Patients with chronic kidney disease on hemodialysis undergo serious changes in social life, in work, eating habits and sexual life, which lead to changes in their physical and emotional integrity. These factors can decrease their quality of life and can make the fragile patient. The weakness is more common among patients with chronic kidney disease, compared to those without such disease due to factors associated with the disease, such as protein wasting, anemia, inflammation, acidosis, and hormonal disorders. Have kidney disease greatly increases the chances of fragility when compared to subjects with normal renal function or those with other chronic diseases. Objective: To identify factors associated with fragility of adults and elderly chronic renal hemodialysis treatment. Method: This is a descriptive, correlational study, a cross-sectional developed into a Renal Replacement Therapy Unit in the state of São Paulo. We assessed 107 participants with chronic kidney disease on hemodialysis, 62 adults and 45 elderly, through the Participants' Characterization Instrument of Fragile Fried Phenotype, the Tilburg Frailty Indicator (TFI), Cognitive Examination Addenbrooke - Revised, the Katz Index and the scale of instrumental activities of daily living Lawton. All ethical principles were respected (Opinion No. 799,212 / 2014). Held correlational analysis and univariate and multivariate logistic regression. Results: Most adults was pre-frail (54.84%) in Phenotype evaluation Fragility Fried and fragile (58.06%) when evaluated by the Tilburg Frailty Indicator. Factors associated with the fragility of adults were fair or poor perceived health status (OR = 0.08; 95% CI 0.02 to 0.35; p = 0.00), female gender (OR = 0.02; 95% CI 0.04 to 0.82; p = 0.02) and dependence for instrumental activities of daily living (OR = 0.81; 95% CI 0.66 to 0.99; p = 0.04). Already the elderly proved fragile (64.44% and 73.33%) in the application of Fried Fragile Phenotype and Tilburg Frailty Indicator, respectively. Aspects associated with frailty were: perception of fair or poor health status (OR = 0.06; 95% CI 0.005 to 0.87; p = 0.00) and cognitive impairment (OR = 0.69; 95% CI 0, 52 to 0.91; p = 0.00). Conclusion: The factors associated with frailty in adults were fair or poor health perception, female and dependence for instrumental activities of daily living. The elderly were: perception of fair or poor health and cognitive impairment. This study brings the contribution to the health team, the assessment of the level of fragility of adults and seniors living with chronic kidney disease on hemodialysis and the factors associated with the frailty syndrome.